The Modulation of Adaptive Immune Responses by Bacterial Zwitterionic Polysaccharides - Tom Li Stephen; Laura Groneck; Wiltrud Maria Kalka-Moll (International Journal of Microbiology)
The detection of pathogen-derived molecules as foreign particles by adaptive immune cells triggers T and B lymphocytes to mount protective cellular and humoral responses, respectively. Recent immunological advances elucidated that proteins and some lipids are the principle biological molecules that induce protective T cell responses during microbial infections. Polysaccharides are important components of microbial pathogens and many vaccines. However, research concerning the activation of the adaptive immune system by polysaccharides gained interest only recently. Traditionally, polysaccharides were considered to be T cell-independent antigens that did not directly activate T cells or induce protective immune responses. Here, we review several recent advances in “carbohydrate immunobiology”. A group of bacterial polysaccharides that are known as “zwitterionic polysaccharides (ZPSs)” were recently identified as potent immune modulators. The immunomodulatory effect of ZPSs required antigen processing and presentation by antigen presenting cells, the activation of CD4 T cells and subpopulations of CD8 T cells and the modulation of host cytokine responses. In this review, we also discuss the potential use of these unique immunomodulatory ZPSs in new vaccination strategies against chronic inflammatory conditions, autoimmunity, infectious diseases, allergies and asthmatic conditions.